Effectiveness of contact tracing and quarantine on reducing COVID-19 transmission: a retrospective cohort study. (December 2020) - Malheiro, R.; Figueiredo, A.L.; Magalhães, J.P.; Teixeira, P.; Moita, I.; Moutinho, M.C.; Mansilha, R.B.; Gonçalves, L.M.; Ferreira, E.
Abstract: Objectives: Contact tracing and quarantine are common measures used in the management of infectious disease outbreaks. However, few studies have measured their impact on the control of the COVID-19 pandemic. This study aimed to assess the effectiveness of those measures on reducing transmission of severe acute respiratory syndrome coronavirus 2 in a community setting. Study design: The study design is a retrospective cohort study. Methods: A retrospective cohort study of COVID-19 cases notified in Eastern Porto from March 1st to April 30th, 2020 was performed. Intervention and control cohorts were defined based on whether cases were subjected to contact tracing and quarantine measures before the laboratory confirmation of disease. The number of secondary cases per index case and the proportion of cases with subsequent secondary cases were the primary outcomes. Secondary outcomes included the time from symptom onset to specimen collection and the number of close contacts. The analysis was stratified according to whether national lockdown measures had already been implemented. Results: The intervention and control cohorts comprised 98 and 453 cases, respectively. No differences were observed concerning primary outcomes. The intervention group had a shorter time between symptom onset and specimen collection (median: 3 days, interquartile range [IQR]: 1–6, vs. median: 5 days, IQR: 2–7, P -value = 0.004) and fewer close contacts (median: 0, IQR: 0–2, vs. median: 2, IQR: 1–4, P -value<0.001). The stratified analysis returned similar results. Conclusion: Local public health measures were effective in reducing the time between symptom onset and laboratory diagnosis and the number of close contacts per case. No effect was apparent on secondary case figures, suggesting that further measures may be required. Highlights: No evidence was found that contact tracing reduces the number of secondary cases. Contact tracing and quarantine allow for a faster diagnosis of symptomatic contacts. Local measures are effective at reducing the number of high-risk contacts. Household members of COVID-19 cases are a particularly susceptible population.